Transforming small and medium‐sized enterprises to address the climate emergency: The case for values‐based engagement. (4th May 2022) - Hampton, Sam; Blundel, Richard; Wahga, Aqueel; Fawcett, Tina; Shaw, Christopher
Abstract: Collectively, small and medium‐sized enterprises (SMEs) make a significant contribution to carbon emissions. Transformative changes are needed to achieve Net Zero amongst the SME community, presenting policymakers and practitioners with a complex and largely unresolved set of challenges. In this paper, we investigate the unexploited potential of human values in facilitating these changes, with a particular focus on the role and experiences of specialist intermediaries, such as business advisors, as agents of change. The paper reports on four linked, transdisciplinary research projects, which tested and validated a values‐based intervention in collaboration with businesses and advisors, designed to promote more effective, long‐term journeys towards Net Zero. Our study connects research evidence on SME support with key insights from values literature, including the emerging concepts of values practices and values work. We discuss outcomes from the four projects, and the broader implications for research, policy, and practice.